THE EFFECT OF ANDALIMAN EXTRACT (ZANTHOXYLUM ACANTHOPODIUM DC) ON THE HISTOLOGY OF THE STZ-INDUCED DIABETES MELLITUS RATS - Maco Chan Adnan; Albert Albert; Gultom Angelina Aprilia; Purba Mellenia; Sitepu Enda; Chiuman Linda; Kotsasi Fransisca (Universitas Negeri Gorontalo, 2022)
Diabetes is a chronic disease that occurs when the pancreas cannot produce enough insulin or the insulin produced by the body cannot be used effectively. In one study it was shown that testicular weight, sperm count, and sperm motility were significantly reduced due to diabetes. This study aimed to determine the effectiveness of methanol extract and ethyl acetate and n-hexane fractions of andaliman (Zanthoxylum acanthopodium DC) on the histopathological features of Streptozotocin-induced rat kidney (Rattus novergicus). The study used 30 white rats weighing 150-260g aged 2-3 months. The test was divided into 6 groups, namely, without treatment given STZ 45 mg/KgBW + Metformin 50 mg/kgBW (Standard), only STZ 45 mg/KgBW (negative control), given STZ 45 mg/KgBW + methanol extract andaliman 300 mg/ kgBW (Menthanol), administration of STZ 45 mg/KgBW + ethyl acetate fraction andaliman 300 mg/kgBW (Ethyl Acetate), and administration of STZ 45 mg/KgBW + n-hexane fraction andaliman 300 mg/kgBW (n-hexane). The extract was administered for 14 days and on the 15th day, the rats were sacrificed and their testes were taken and the histological process was carried out. The results showed that presenting ethyl acetate fraction of andaliman fruit (Z. acanthopodium DC) could prevent the level of testicular damage in diabetic patients.